Spontaneous vaginal cuff dehiscence and evisceration of multiple organs: A case report - Zhou, Yan (Medicine (Baltimore), 2018)
RATIONALE: Vaginal cuff dehiscence and evisceration constitute a rare but potentially life-threatening event that usually occurs in postmenopausal patients who have undergone hysterectomy. This is a valuable case of spontaneous transvaginal evisceration without pelvic surgery history. PATIENT CONCERNS: A 74-year-old postmenopausal woman with an obstetric history of 7 full term vaginal deliveries, experienced sudden evisceration when she attempted to defecate. DIAGNOSES: Spontaneous vaginal cuff dehiscence and multiorgan evisceration. INTERVENTIONS: After physical examination and fluid resuscitation, the patient had underwent the Hartmann's procedure, total hysterosalpingo-oophorectomy, sacrocolpopexy, and posterior colporrhaphy. OUTCOMES: The patient recovered well and the constipation symptoms have significantly improved. One-year follow-ups examination revealed complete healing of the vaginal cuff, and there was no evidence of prolapse. LESSONS: We report a case of spontaneous vaginal cuff evisceration without pelvic surgery history but with constipation and redundant sigmoid colon. After resecting the necrotic sigmoid colon, the patient's constipation symptoms significantly improved. It is reasonable to speculate that the etiology was related to severe sigmoidocoele.